Implementation of the C45 Algorithm for Predicting the Visit Rate of Patients at dr. Daniel Bengkulu - Jery Rohmadan Wahari; Yuza Reswan (Penerbit Jurnal Indonesia, 2022)
In the business world, every clinic must of course be able to compete and think about how the clinic can continue to grow and expand its business scale. However, the problems faced by companies have varying degrees of difficulty and complexity, ranging from very simple problems to very complex problems. The general objective of this research is to fulfill one of the requirements for writing a thesis to obtain a Bachelor's degree in Computer Science at the Informatics Engineering Study Program, University of Muhammadiyah Bengkulu. Application of predictive application of patient visit rate at Dr. clinic. This Daniel can be used to help Dr. Daniel in predicting the level of patient visits, both new patients and old patients as well as the distance from the patient's home to Dr. Daniel. So this application can be used as a reference to predict patient visits on the next day. The MySQL database can accommodate information and data that is input into this patient visit rate prediction application. From the results of the tests carried out, it can provide convenience for Dr. Daniel in predicting the level of patient visits so that he can provide good service to patients.